2020
DOI: 10.5565/rev/ensciencias.2888
|View full text |Cite
|
Sign up to set email alerts
|

Trabajar la argumentación a través de un juego de rol: ¿debemos instalar el cementerio nuclear?

Abstract: RESUMEN • En este artículo se analizan las operaciones argumentativas llevadas a cabo por profesorado en formación inicial durante un juego de rol sobre la posible instalación de un cementerio nuclear y se examinan los tipos de conocimiento que ponen en juego al construir sus argumentos en la búsqueda de una decisión final. Los participantes son estudiantes de los grados en Educación Infantil y Primaria de tres universidades españolas. La toma de datos incluye las grabaciones de la implementación del juego de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 38 publications
0
11
1
5
Order By: Relevance
“…Based on the scientific literature, we find several precedents on gamification in initial teacher education [35][36][37][38][39], although it is only on rare occasions in these precedents that any gamified activity is used to work on current controversial topics, such as in the studies by Clarke et al [40] or Nicholson [28]. However, pre-service and in-service teachers still show a high level of ignorance about the educational use of gamified strategies [41,42].…”
Section: Gamification: Innovative Methodologies In Initial Teacher Tr...mentioning
confidence: 99%
“…Based on the scientific literature, we find several precedents on gamification in initial teacher education [35][36][37][38][39], although it is only on rare occasions in these precedents that any gamified activity is used to work on current controversial topics, such as in the studies by Clarke et al [40] or Nicholson [28]. However, pre-service and in-service teachers still show a high level of ignorance about the educational use of gamified strategies [41,42].…”
Section: Gamification: Innovative Methodologies In Initial Teacher Tr...mentioning
confidence: 99%
“…Involving both pre-test and post-test data collection and both qualitative and quantitative analysis and interpretation of results (Creswell, 2014). Given that this is not an experimental research, in this work there was no control group, as in other similar works on role play and nuclear energy (Crujeiras-Pérez et al, 2020;Evren & Aycan, 2018;Freire at el., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have examined the use of role play for exploring issues related to nuclear energy. Crujeiras-Pérez et al (2020) found that scientific/technological knowledge was the second most common type of knowledge used by PPTs for argumentation in the context of a role play activity on establishing a nuclear cemetery, although it was not always correct from a scientific point of view. Outside of the role play context, Ozturk and Yilmaz-Tuzun (2017) found that arguments based on scientific and/or technological questions were used by a minority of pre-service science teachers, whose reasoning was more likely to focus on the risks of the use of nuclear energy and on social and ecological aspects.…”
Section: Pre-service Teachers and The Issue Of Nuclear Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Etapas iniciales de la educación como la EP no están ausentes de práctica científica. Existen ejemplos en la literatura que sustentan sus beneficios (así como sus limitaciones) tanto para la indagación (Pedaste et al, 2015;Parrilla Maldonado et al, 2017;Aguilera et al, 2018;Kruit et al, 2018) como para la argumentación (Lazarou et al, 2016;Crujeiras-Pérez et al, 2020) y la modelización (Pujol-Vilallonga et al, 2006;Acher et al, 2007;Gómez Galindo et al, 2007).…”
Section: Las Prácticas Científicasunclassified